Collaborative Governance In Handling Industrial Relations In The Manpower Department Of West Bandung Regency - Karunna, Winston (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study investigates the application of Collaborative Governance in managing industrial relations at the West Bandung Regency Manpower Service, focusing on the district's efforts to create harmonious relations between workers and employers amidst its evolving social and economic environment. The main objective of the research is to assess the effectiveness of collaboration among government, employers, and labor unions in resolving industrial disputes, while identifying the key factors that impact the success of such collaborations. Employing a Collaborative Governance approach for human resource management, the research highlights the importance of involving multiple stakeholders in policy formulation and problem-solving, emphasizing transparency, trust-building, and open communication. The study evaluates the mediation mechanisms utilized by the Manpower Service, identifying both strengths and challenges such as power imbalances, limited resources, and varying levels of stakeholder engagement. Results indicate that while the implementation of collaborative processes has led to some improvements in industrial dispute resolution, challenges remain in ensuring equitable participation from all parties. The findings suggest that refining collaborative models could lead to more effective conflict resolution, fostering long-term stability in industrial relations. Ultimately, this research aims to provide valuable insights into how Collaborative Governance can enhance worker welfare, improve employer- employee relations, and contribute to the region's economic resilience.